The Impact of Building Façade Designs on Noise Reduction: A Case Study from Iraq - Almusawi, Tahrir Taki Ali; Alomare, Ashwaq Fadhel Muhkaber; Kadhum, Lina Kifah; Alkhayat, Zainab Qahtan Abd (Journal of engineering and sustainable development (Online), 2025)
This paper explores the impact of building facade designs on noise reduction in Baghdad city, where noise is a growing concern due to population growth. It identifies the influence of geometrical design details in the façade of the building and the site layout on noise reduction. The paper employs a case study, examining a two-story dwelling in a mixed-use area located near a busy road. Different acoustic measurements were conducted using a sound level meter, AutoCAD software, and additional analysis tools to assess noise levels inside and outside the dwelling. The findings indicate that balconies, noise barriers, plantations, and site layout can significantly reduce noise exposure within the dwelling. The paper emphasizes the importance of acoustic comfort in design to enhance the quality of urban living areas. As urban areas continue to expand, this research provides architects and urban designers with insights to help improve the quality of life for residents and create quieter indoor environments, and also ensure more pleasant outdoor spaces.